The role of oestrogen and progesterone receptors in breast cancer – immunohistochemical evaluation of oestrogen and progesterone receptor expression in invasive breast cancer in women - Badowska-Kozakiewicz, Anna; Patera, Janusz; Sobol, Maria; Przybylski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: Expression of oestrogen and progesterone receptors is a very powerful and useful predictor. Because the response rate to hormonal treatment in breast cancer is associated with the presence of oestrogen and progesterone receptors, assessment of the receptor expression profile allows for prediction of breast cancer response to hormonal treatment. The aim of this study was to assess whether the expression of receptors for oestrogen (ER) and progesterone (PR) in the tumour tissue of patients with invasive breast cancer correlated with tumour histological type, histological grade of malignancy, tumour size, and lymph node status. Material and methods: Materials consisted of histological preparations derived from patients treated for invasive breast cancer. Evaluations were conducted with histopathological and immunohistochemical methods using suitable antibodies. Results: Among 231 cases of breast cancer 18 invasive lobular carcinomas (ILC) and 213 invasive ductal carcinomas (IDC) were diagnosed. Taking the histological type of tumour into account, oestrogen receptor-positive reaction was observed in 74.2% of IDC and 77.8% of ILC, and the positive response to PR was observed in 67.1% of IDC and 61.1% of ILC. Considering the histological grade, ER- in the largest percentage (72%) was observed in second-grade (G2) invasive carcinomas. Similarly, PR expression (75%) was found in the largest percentage in second-grade (G2) carcinomas. Based on our own studies and data from literature, it appears that the ER (+) status is an indicator of good prognosis, because it points to a less aggressive cancer, in which overall survival and disease-free time is longer in comparison with ER (–) tumours. Conclusions : Determination of ER status may, therefore, have significant clinical value and is widely used in routine pathological diagnostics.